2017
DOI: 10.1590/0102-311x00084216
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and modeling of race and health in Brazil: continuing the discussion

Abstract: Recent reviews have discussed the conceptualization of race in health studies in Brazil. This review further documents and discusses specific measurement and modeling issues with regard to race and how this can impact result interpretation. Three scientific databases were used to search the literature on race and three health outcomes. The search yielded 38 empirical studies on birth outcomes, self-rated health, and weight. Results suggest that, while there are racial patterns in the overall literature, concep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
3
0
2
Order By: Relevance
“…While there is no biological basis for an association between these constructs and health, 64 ethnicity, caste and race are proxies for the embodiment of xenophobia, casteism and racism in their structural, cultural and interpersonal forms. 65 Data from the US context, for example, observed that in areas where mortality rates are highest, the fraction of black residents is larger. 66 These findings may be extrapolated to the Brazilian context, where racial inequality and segregation are reflected in social disadvantage 65 and health inequities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While there is no biological basis for an association between these constructs and health, 64 ethnicity, caste and race are proxies for the embodiment of xenophobia, casteism and racism in their structural, cultural and interpersonal forms. 65 Data from the US context, for example, observed that in areas where mortality rates are highest, the fraction of black residents is larger. 66 These findings may be extrapolated to the Brazilian context, where racial inequality and segregation are reflected in social disadvantage 65 and health inequities.…”
Section: Discussionmentioning
confidence: 99%
“… 65 Data from the US context, for example, observed that in areas where mortality rates are highest, the fraction of black residents is larger. 66 These findings may be extrapolated to the Brazilian context, where racial inequality and segregation are reflected in social disadvantage 65 and health inequities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A variável raça/cor pode apresentar erros de classificação, transitoriedade ao longo do tempo e imprecisão conceitual para estudos em saúde [17][18][19][20] . No entanto, procedeu-se à análise epidemiológica conforme o uso recomendado desta variável na literatura.…”
Section: Gruposunclassified
“…Nesta perspectiva, a raça é compreendida como um produto das relações históricas, socioculturais e de ancestralidade, que contribuem para a formação identitária, contrapondo-se às identidades baseadas em diferenciações genéticas [15][16][17][18][19] e é utilizada em estudos epidemiológicos para operacionalização do construto "etnia".…”
Section: Introductionunclassified